Optimization of electrochemical pre-treatment for essential oil extraction from lemon myrtle (B. citriodora) leaves by response surface methodology - Hamzah, Muhammad Hazwan; Ibrahim, Siti Khairunnisa; Mohd Nor, Mohd Zuhair; Hamzah, Adila Fazliyana Aili; Shamsudin, Rosnah; Md Ali, Abd Halim (Springer, 2023)
Backhousia citriodora essential oils are gaining market share due to their diverse applications, which include disease treatment, food flavouring and disinfectants. The study aims to determine the optimal parameters of electrochemical pre-treatment performed prior to Soxhlet extraction, namely, voltage, particle size, and pre-treatment time using response surface methodology. The Soxhlet extraction was conducted for five hours using n-hexane as solvent and a solid to solvent ratio of 1:10. The essential oil was then extracted at 60 °C using a rotary vacuum evaporator. Results predicted a maximum oil yield of 5.88% for the optimal voltage (5 V), pre-treatment time (5 min), and particle size (100 μm). The oil yield for treated samples is 5.85% versus 6.13% for untreated samples. Physical analysis has showed that the characteristics of both untreated and treated samples are similar. The functional group detected for B. citriodora by Fourier transform infrared spectroscopy was C=O, C–H, and C–O and O–H. Scanning electron microscope shows that electrochemical pre-treatment has opened oil gland and caused cell wall to flatten. Further research should implement the proposed recommendations to obtain a higher yield utilising this pre-treatment procedure.